Comparative cytogenetics of serrasalmidae (Teleostei: Characiformes): The relationship between chromosomal evolution and molecular phylogenies - Feldberg, Eliana; Ota, Rafaela Priscila; Nakayama, Celeste Mutuko; Porto, Jorge Ivan Rebelo; Campos, Alber Sousa; Ribeiro, Leila Braga; Favarato, Ramon Marin (PLoS ONE, 2021)
Serrasalmidae has high morphological and chromosomal diversity. Based on molecular hypotheses, the family is currently divided into two subfamilies, Colossomatinae and Serrasalminae, with Serrasalminae composed of two tribes: Myleini (comprising most of pacus species) and Serrasalmini (represented by Metynnis, Catoprion, and remaining piranha’s genera). This study aimed to analyze species of the tribes Myleini (Myloplus asterias, M. lobatus, M. rubripinnis, M. schomburgki, and Tometes camunani) and Serrasalmini (Metynnis cuiaba, M. hypsauchen, and M. longipinnis) using classical and molecular cytogenetic techniques in order to understand the chromosomal evolution of the family. The four species of the genus Myloplus and T. camunani presented 2n = 58 chromosomes, while the species of Metynnis presented 2n = 62 chromosomes. The distribution of heterochromatin occurred predominantly in pericentromeric regions in all species. Tometes camunani and Myloplus spp. presented only one site with 5S rDNA. Multiple markers of 18S rDNA were observed in T. camunani, M. asterias, M. lobatus, M. rubripinnis, and M. schomburgkii. For Metynnis, however, synteny of the 18S and 5S rDNA was observed in the three species, in addition to an additional 5S marker in M. longipinnis. These data, when superimposed on the phylogeny of the family, suggest a tendency to increase the diploid chromosome number from 54 to 62 chromosomes, which occurred in a nonlinear manner and is the result of several chromosomal rearrangements. In addition, the different karyotype formulas and locations of ribosomal sequences can be used as cytotaxonomic markers and assist in the identification of species. © 2021 Favarato et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.